Appendicitis among Patients Admitted to the Department of Surgery of a Tertiary Care Centre: A Descriptive Cross-sectional Study - Kishor Kumar Deo; Prajwala Yogi; Aliska Niroula; Sujata Maharjan (Journal of Nepal Medical Association, 2023)
Introduction: The prevalence of appendicitis is widespread among both adult and pediatric populations. Despite being so common, its diagnosis remains difficult. Initially, acute appendicitis is managed conservatively. To reduce morbidity and mortality, surgery must be performed promptly. The main objective of the study is to find out the prevalence of appendicitis among patients admitted to the department of surgery of a tertiary care centre.